POWER RELATIONS, HEGEMONY AND IDEOLOGY - Elias Garcia, Tatiane (Revista Gênero e Interdisciplinaridade, 2024)
This research aims to explore three fundamental works that address interconnected aspects of political, philosophical and social thought. “Fascism”, by Evguiéni B. Pashukanis, released in 2020, offers a critical analysis of the ideological roots and social implications of fascism. Then, “Philosophy, Ideology and Social Science - Essays on Denial and Affirmation”, by István Mészáros, published in 1993, highlights the contradictions of the capitalist system and potential social transformations. Finally, “The German Ideology”, by Karl Marx and Friedrich Engels, written in the 19th century, provides a theoretical basis for understanding historical materialism and criticizing the dominant ideology. The research seeks to draw connections between these works to enrich the understanding of contemporary social and political dynamics.